Analisis pertumbuhan dan kemampuan reduksi limbah larva tentara hitam (Hermetia illucens) pada solid decanter, ampas kelapa, ampas sagu, dan limbah sisa makanan - Novianti Adi Rohmanna; Dessy Maulidya Maharani; Zuliyan Agus Nur Muchlis Majid (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
BSF larvae were the agents capable of breaking down large amounts of organic waste. These larvae were known to reduce organic waste effectively and produced larval biomass. The substrate type was one of the factors that could affect the larvae's performance. This study aimed to determine the effect of the type of substrate or organic waste on the growth and waste reduction performance of larvae. Larvae were reared for ten days on several organic wastes, including food waste, solid decanter, coconut pulp, and sago pulp. The growth rate, bioconversion rate, waste reduction index, and feed conversion ratio were analyzed. The larvae with the best reduction performance were then analyzed for protein and fat on days 7 and 10. The results showed that BSF larvae in food waste showed more growth than in other wastes. BSF larvae in food waste showed a high waste reduction performance, while BSF larvae in solid decanter showed poor waste reduction performance. The BSF larval biomass in food waste contained high levels of protein and fat (38.94 % and 42.86 %, respectively).